2009
DOI: 10.1093/carcin/bgp135
|View full text |Cite
|
Sign up to set email alerts
|

Decoy receptor 3, upregulated by Epstein-Barr virus latent membrane protein 1, enhances nasopharyngeal carcinoma cell migration and invasion

Abstract: Decoy receptor 3 (DcR3), a member of tumor necrosis factor receptor superfamily, has been implicated in tumorigenesis through its abilities to modulate immune responses and induce angiogenesis. Epstein-Barr virus (EBV), a ubiquitous gamma-herpesvirus, is associated with malignancies including nasopharyngeal carcinoma (NPC). Previous studies show that DcR3 is overexpressed in EBV-positive lymphomas and Rta, an EBV transcription activator, can upregulate DcR3 in Burkitt lymphoma cell lines. However, DcR3 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…Both LMP1-mediated transcriptional, posttranscriptional and posttranslational regulation of cellular targets could contribute to the capacity of LMP1 to promote spreading of tumor cells: (1) LMP1 causes loss of junctional plakoglobin in nasopharyngeal carcinoma (NPC) cells and initiates a cadherin switch [[52]]. (2) LMP1 upregulates decoy receptor 3, a member of the TNFR superfamily, which enhances NPC cell migration and invasion [[43]]. (3) LMP1 down-regulates E-cadherin gene expression and induces cell migration activity by using cellular DNA methylation machinery [[45]].…”
Section: Discussionmentioning
confidence: 99%
“…Both LMP1-mediated transcriptional, posttranscriptional and posttranslational regulation of cellular targets could contribute to the capacity of LMP1 to promote spreading of tumor cells: (1) LMP1 causes loss of junctional plakoglobin in nasopharyngeal carcinoma (NPC) cells and initiates a cadherin switch [[52]]. (2) LMP1 upregulates decoy receptor 3, a member of the TNFR superfamily, which enhances NPC cell migration and invasion [[43]]. (3) LMP1 down-regulates E-cadherin gene expression and induces cell migration activity by using cellular DNA methylation machinery [[45]].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of LMP1 in nasopharyngeal carcinoma indicated that LMP1 can enhance nasopharyngeal carcinoma cell migration and invasion. Moreover, the human Fab-based immune-conjugate specific for the LMP1 extracellular domain can inhibit nasopharyngeal carcinoma growth both in vitro and in vivo (14,15). These finding suggest that LMP1 may play an important role in the progression of ENKTL.…”
Section: Introductionmentioning
confidence: 84%
“…These findings strongly highlight the therapeutic implications of targeting LMP1. LMP1 has been involved in various events of tumor progression, through regulating numerous oncogenic signaling pathways such as nuclear factor-kappaB, phosphatidylinositol 3-kinase, AKT, and mitogen-activated protein kinases [17,25,32,33]. Terrin et al [34] reported that LMP1 simultaneously modulates multiple signal transduction pathways in B cells to transactivate the hTERT promoter and enhance telomerase activity.…”
Section: Discussionmentioning
confidence: 99%